Mobile application for children with visual processing disorder / Muhd Amir Rashidi Hamzah - Hamzah, Muhd Amir Rashidi (2015)
This paper present about the use of smartphone and its technology in order to aid the children with learning disabilities in their learning process. Each type of smartphone has different operating system that power them. Online service provide are also differ from one to another, as the number of user increase, the number of application available in online store are also keep increase. One interesting benefit that mobile app give to user is it can be used for educational tool, this is not just for normal people but people with disabilities can also use it, in this research the focus will be on children with visual processing disorder. Visual processing disorder are usually mistaken with other specific learning disabilities which is dyslexia and dyspraxia whereas it was a learning disabilities that stand firm on its own. This disabilities are usually hard to find in children because most of parents and teacher does not know what their children and student problem were until they have taken the child to specialist, furthermore there are no proper guidelines for them to teach the kids normally. In addition visual processing disorder can be further divided to 8 category which is visual discrimination issues, visual figure discrimination issues, visual sequencing issue, visual motor processing issues, long or short term memory issues, visual spatial issues, visual closure issues and letter and symbol reversal issues. A mobile app for the said children will be develop in this project using mobile application development life cycle and will only focus on 3 area that is visual discrimination issues, visual sequencing issues as well as visual motor processing issues.